Successful treatment of Erdheim–Chester disease with combination of interleukin‐1‐targeting drugs and high‐dose glucocorticoids. Issue 1 (January 2014) - Darstein, F.; Kirschey, S.; Heckl, S.; Rahman, F.; Schwarting, A.; Schuchmann, M.; Galle, P. R.; Zimmermann, T.
Abstract Erdheim–Chester disease (ECD) is a rare histocytic disorder. We report a case of a 45‐year‐old male ECD patient with severe clinical manifestation (urinary obstruction due to retroperitoneal mass with hydronephrosis, involvement of long bones) and central nervous system involvement (hemiparesis, aphasia and diabetes insipidus). Diagnosis was confirmed by typical clinical, radiological and histological findings. Under immunosuppressive therapy with prednisolone and interleukin‐1A receptor antagonist (Anakinra, Kineret, Swedish Orphan Biovitrum AB, Stockholm, Sweden), a rapid improvement of the patients' symptoms and condition was observed. This is the first report of a successful combination therapy of Anakinra and glucocorticoids. Furthermore, current literature about ECD and treatment options are discussed.